2022
DOI: 10.3390/curroncol29090511
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prognostic Impact of Postoperative Complications in Patients with Advanced Gastric Cancer Receiving Neoadjuvant Chemotherapy

Abstract: Background: Neoadjuvant chemotherapy is important to improve the prognosis of patients with advanced gastric cancer. However, it may result in postoperative complications (POCs). The aim of this study is to evaluate risk factors and prognostic impact of POCs in patients receiving neoadjuvant chemotherapy. Methods: We retrospectively collected clinical information of patients who underwent curative gastrectomy after receiving neoadjuvant chemotherapy between 2011 and 2018. Overall survival (OS) was analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Few studies have investigated the use of preoperative parameters such as albumin levels to predict the risk of postoperative recurrence and complications in patients undergoing neoadjuvant therapy [24]. Yu et al [25] found that low preoperative albumin levels were a risk factor (p = 0.033) for postoperative complications in patients undergoing curative gastrectomy after neoadjuvant chemotherapy, while Migita et al [14] found a correlation between decreased serum albumin levels after neoadjuvant therapy and survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the use of preoperative parameters such as albumin levels to predict the risk of postoperative recurrence and complications in patients undergoing neoadjuvant therapy [24]. Yu et al [25] found that low preoperative albumin levels were a risk factor (p = 0.033) for postoperative complications in patients undergoing curative gastrectomy after neoadjuvant chemotherapy, while Migita et al [14] found a correlation between decreased serum albumin levels after neoadjuvant therapy and survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative recovery and complications are crucial indices of short-term safety and efficacy. Neoadjuvant therapy can increase the incidence of myelosuppression and malnutrition, decrease immune function, and aggravate tissue edema, fibrosis, and chronic inflammation, further increasing structural complexity, all of which can increase the risk of poor surgical safety and POCs [ 35 ]. Hong et al [ 36 ] reported that esophagectomy was safe and feasible following NICT for locally advanced esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a global health problem and the second leading cause of death in developed countries ( 1 ). A significant part of that problem is gastric cancer, being the fifth most common cancer worldwide ( 2 ). Despite numerous improvements in systemic treatment, patients diagnosed at an advanced stage have poor prognosis ( 3 ), and in such cases, medical procedures may be more of a palliative nature ( 4 ).…”
Section: Introductionmentioning
confidence: 99%